Research and Application of Broadband Matching Technology for Single Crystal Underwater Acoustic Transducer. Issue 1 (January 2021) - Li, Haonan; Zheng, Hong; Tang, Yunfeng; Zhang, Xufeng
Abstract: To solve the broadband matching problem of underwater acoustic transducer, a matching method based on network theory analysis and Monte Carlo algorithm is studied in this paper. In this study, the network function expression is obtained by designing the matching network, and then the objective function is constructed. Monte Carlo algorithm is used to find the optimal solution of the matching network parameters to realize the broadband matching of a piezoelectric single crystal underwater acoustic transducer. By comparing the broadband matching of traditional piezoelectric ceramic transducer, the performance of single crystal material transducer is better after matching, that is to say, it can obtain good gain and broaden the frequency band at the same time. The whole matching process is simple and efficient, the matching effect is good. It provides a feasible reference for broadband matching of new single crystal underwater acoustic transducer.